AbMTM: Post COVID-19 Adventure-based Mental Toughness Training Model / Mohd Shariman Shafie ... [et al.] - Shafie, Mohd Shariman; Md Taff, Md Amin; Zainol, Zuraidah; Mat Rasid, Siti Musliha (2021)
To date, cases in COVID-19 have accelerated with new cases surfacing almost every day. Along with the issue, numerous cases related to mental health problem such as levels of anxiety, depression and attempting suicides were recorded. These problems claim to be associated with individual mental toughness. Work on this matter, it is a call to invent solutions. The innovation of Adventure-based Mental Toughness Model (AbMTM) rooted in the systematic modified Design and Development Research (DDR: Saedah et. al., 2020). A total of 14 field's experts and 507 respondents was involved in a series of analysis using Structural Equation Modelling (SEM). The AbMTM is a validated model with the excellence model fit (GoF). The innovation of AbMTM potentially contributes to Malaysian active adventure-based training practitioners and professional. AbMTM also significantly becomes a part of the solutions in purpose to regain or improve mental toughness to more than 50% Malaysian population that involved with active recreation (IYRES: Sports Index 2017, 2018, 2019) in post pandemic era. AbMTM useful to the adventure-based training program practitioners and professional to redesign and adapt their training programs that suit the current training needs in post pandemic era. AbMTM offers new collaboration mental toughness attributes and as communication tools to understand the development throughout the intervention of adventure-based training program. The term of adventure-based training that commonly refers to teambuilding, team cohesiveness and individual development is now shifted to be more relevant towards challenges and opportunities after pandemic outbreak. To conclude, with AbMTM, adventure-based training industry in Malaysia are ready to accept change and evolve with time in post pandemic era.